Inflammasomes in neuroinflammatory and neurodegenerative diseases - Sofie Voet; Sahana Srinivasan; Mohamed Lamkanfi; Geert van Loo (EMBO Molecular Medicine, 2019)
Abstract Neuroinflammation and neurodegeneration often result from the aberrant deposition of aggregated host proteins, including amyloid‐β, α‐synuclein, and prions, that can activate inflammasomes. Inflammasomes function as intracellular sensors of both microbial pathogens and foreign as well as host‐derived danger signals. Upon activation, they induce an innate immune response by secreting the inflammatory cytokines interleukin (IL)‐1β and IL‐18, and additionally by inducing pyroptosis, a lytic cell death mode that releases additional inflammatory mediators. Microglia are the prominent innate immune cells in the brain for inflammasome activation. However, additional CNS‐resident cell types including astrocytes and neurons, as well as infiltrating myeloid cells from the periphery, express and activate inflammasomes. In this review, we will discuss current understanding of the role of inflammasomes in common degenerative diseases of the brain and highlight inflammasome‐targeted strategies that may potentially treat these diseases.